Penerapan Permainan Sirkuit Sensorik Berbasis Irama Lagu Untuk Meningkatkan Kecerdasan Kinestetik Anak Usia Dini - Sofia Nur Rohmah; Heri Yusuf Muslihin; Resa Respati (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to determine the application of song rhythm-based sensory circuit games in improving the kinesthetic intelligence of early childhood, especially in the aspects of balance and body coordination. The method used in this study is Classroom Action Research (CAR) with the Kemmis and Mc Raggart models, which were implemented in two cycles. The research subjects in this study were 12 children from group B1 with an age range of 5-6 years at PGRI Galunggung Tasikmalaya Kindergarten. Data collection techniques used observation and documentation sheets with data analyzed qualitatively and quantitatively. The results of the research that has been done show an increase in children's kinesthetic intelligence abilities. In the pre-cycle stage, the average achievement was 41.6% with the MB (Starting to Develop) category. After the implementation of song rhythm-based circuit games, there was an increase in cycle I to 72.9%, with the BSH (Developing According to Expectations) category. And in cycle II it reached 86.1% with the BSB (Developing Very Well) category. In addition, the teacher's ability to plan and implement learning has also increased. It can be concluded that rhythm-based sensory circuit training can be an effective and enjoyable method for enhancing kinesthetic intelligence in early childhood. This method also supports teachers in creating active and meaningful learning